Finding Eva Hoffman in Lost in Translation - Tucker, Herbert F. (Studia Anglica Posnaniensia, 2025)
In her 1989 Lost in Translation: A Life in a New Language, Eva Hoffman graphs so articulately the asymptotic narrative that brings her younger self into alignment with the retrospective self who writes the book, that there seems little for the literary interpreter to do but restate the author’s lucid insights. Still, appreciative criticism may yet illuminate the artistry with which this work, written by a gifted intellectual who was also a talented amateur musician, is composed: major movements at the macro-level, scrupulous performance by the page and the phrase. Hoffman not only declares here and there what her “life in a new language” means, but also manifests that meaning as an intention unfolding through the design and sequence of its leading episodes. Furthermore, her self-conscious handling of English, including its seasoning by vestigial and not-quite-translated words from Polish and other tongues, lets the verbal medium strike at times a deeply textured chord resisting the forward linearity of narrative. Thus Hoffman rehearses in the reader’s company – solicits, indeed, the construing reader’s intimate collusion in – those temporal knots of throwback and anticipation which inform her book’s most moving passages.